The New demographic transition : most gains in life expectancy now realized late in life - Eggleston, Karen N. (2012)
Covers the years 1900 - 2007 for the US and 16 other developed countries chosen for the continuity of their mortality data : Australia, Belgium, Canada, Denmark, England and Wales, Finland, France, Iceland, Italy, Nethelands, Northern Ireland, Norway, Scotland, Spain, Sweden and Switzerland. Focuses on demographic statistics including life expectancy at birth and at age 65, the percent of each birth cohort expected to survive to age 65, and the share of the increase in life expectancy at birth realised at age 65. Calculates expected labour force participation for each birth cohort for the US economy, which allows the investigation of how changes in mortality affect labour force participation and work-life as a share of life expectancy. Concludes with a brief discussion of the long-run implications of the new demographic transition.